Rome, Europe, world – roman law as the ratio scripta - Leszczyński, Marcin (Hybris, 2018)
Some legal historians believe that there is a fairly uniform legal tradition in Europe. That conviction is brought about by the research of Roman law’s reception in different countries and its function for canon law. Hence, Roman law is considered to be an actual, historical foundations of different legal orders. In that sense, Roman law takes over a function, already attributed to it in Middle Ages, of ratio scripta. In content it is similar to natural law. What is more, constant reference to the uniform legal tradition can lead to anachronistic opinions on political situation in Europe. In the article I venture an opinion that Roman law should not be a valid reference point for a construction of legal order in Europe – despite the obvious reasons why it could be.